Disparitas Penegakan Hukum di Indonesia (Analisis Kritis Kasus Nenek Minah dalam Perspektif Hukum Progresif) - Murdoko (Faculty of Law Hang Tuah University, 2016)
This paper examines the law enforcement in public domain. The court decisions on many cases often undergo disparities that deny the sense of justice. The disparities increasingly appear when the case comes to people who have political or economic power. However, when the case comes to the poor, who do not have power and so on, the law can be very sharp to enforce. In perspective of the progressive law, the case of Nenek Minah is ideally not relevant to prosecute at the court. In fact, that case shows that the working of the law in Indonesia is still based on the text rather than the context. The law enforcement is solely based on the written provisions (legalistic-positivistic) without paying attention to sociological dimension, so that the law enforcement is still far away from the purpose of law that is able to present the real justice.